The Voltage Control Strategy for Doubly Salient Electromagnetic Generator With Active Rectifier Based on Optimal Current Distribution - Weifeng Liu; Yulong Tao; Xiaoli Meng (IEEE Access)
The doubly salient electromagnetic generator (DSEG) has the advantages of simple structure, high-temperature and high-speed environment adaptability, high reliability, which can build a competitive aerospace brushless DC starting/generation system. The dynamic response of the power generation system with diode rectifier (DR) is limited by the DC-link capacitor and the large time constant of the excitation winding. The adoption of active rectifier (AR) can increase the output power, reduce the copper loss, and improve the system efficiency. Either the excitation current or the armature current can be adjusted to control the output voltage in the generation system with AR. However, adjusting only one of the two currents cannot achieve optimal performance in terms of dynamic response and copper loss. This paper proposes an optimal current distribution control (OCDC) strategy for the active rectifier power generation system, which is based on the back electromotive force (EMF) oriented vector control (BEFOVC) strategy. By using an armature current inner loop to replace the excitation current inner loop and controlling the excitation current according to the minimum copper loss trajectory (MCLT), the OCDC strategy improves the dynamic performance and reduces the copper loss of the DSEG system. Simulations and experiments comparing the traditional voltage control strategy with the proposed strategy verify the feasibility and superiority of the OCDC strategy.